PENGARUH KOMPETENSI, INTEGRITAS, OBJEKTIVITAS DAN ETIKA PEMERIKSAAN TERHADAP KUALITAS AUDIT - Yosafat Hartadi P.S (UNHI Press, 2021)
Audit quality is the result obtained from the audit process in the government and private sectors, especially the inspectorate. Audits relate to the accountability carried out by each institution, both private and government. Accusations of fraud against the auditor profession in the community in conducting audit results process can determine quality audit result. quality audit is carried out to assess that the implementation of the government or the exercise of reign operational activities has been done accourdingly to applicable rules. Science purpose to specify the affect of auditor competence, integrity, objectivity and audit ethics on audit quality. The population in this study were all internal auditors at the Inspectorate of Tabanan Regency and Gianyar Regency, Bali Province and samole by using the saturated sample method or census. The sample method used, namely saturated sample or census with 62 respondents. Using data analysis techniques this multiple linear regression. Based on research result, I can see that overall competency test, integrity, objectivity and audit ethics have a positive effect on the quality of auditors' audits.